The Effect of the Ergonomics of the Reggio Emilia Approach and Mastery Motivation on Early Childhood Independence - Nelva Rolina; I Nyoman Sudana Degeng; Sulthoni Sulthoni; Dedi Kuswandi (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2026)
This study examines the effect of the Ergonomic of Reggio Emilia Approach (EoREA) and Mastery Motivation (MM) on Early Childhood Independence (ECI). Thus, the purpose is to determine the main and interaction effects of the treatment variables on ECI. There are three variables in the study, namely: the independent variable (EoREA), the moderator variable (MM), and the dependent variable (ECI). The quasi-experimental study used a 2 x 2 factorial design, and the subjects were students from Play Group. The results showed a difference in the ECI between learning using play environment arrangements according to the EoREA and NEoREA, as indicated by a significant F value (F = 20.441; p < 0.05). There was also a difference in the ECI between students with high and low MM, as indicated by F = 4.580; p < 0.05. It is also known that there was an interaction between the EoREA model and MM on the ECI, as evidenced by F = 9.478, p < 0.05. Thus, it can be concluded that the three hypotheses in this study have been proven, so that the EoREA model assisted by MM can be applied to stimulate ECI.